MC21 v.10 – coupled-radiation Monte Carlo transport solver with support for multiphysics simulations - Griesheimer David P.; Gill Daniel F.; Nease Brian R.; Pavlou Andrew; Stedry Mark H.; Thompson Jason T.; Burke Paul E.; Dobreff Peter S. (EPJ Nuclear Sciences & Technologies)
Over the past decade, the development of the MC21 Monte Carlo radiation transport solver has focused on extending the functionality of the code beyond static calculations of reactivity and reaction rate distributions, as well as improving accuracy, performance, and scalability. Notable improvements include enhanced interaction physics models, efficient model representation and tracking algorithms, support for coupled physics calculations using both in-line and externally coupled feedback modules, and the development of native visualization and results post-processing tools. As a result of these improvements, MC21 v.10 provides a comprehensive analysis framework that allows complicated engineering problems to be solved with minimal reliance on external tools.